Aleatlón: la prueba del atleta completo - Aragón Vargas, Luis Fernando (1987)
In the world of fitness, that is, everything related with gyms and training, different methods become popular and create a large following. One of the most popular at the beginning of the XXI century is CrossFit, a combination of tests in different categories being used not only as a training method but which has become a sports discipline attracting competitors from dozens of countries around the world. Interestingly, an original description of this activity had been published 25 years ago at the University of Costa Rica. It is made available hereby to facilitate access to those interested in the origin of CrossFit.